Taxonomy of Colophon Gray (Coleoptera: Lucanidae): new species and a status change - Jacobs, Carmen T.; Scholtz, Clarke H.; Strümpher, Werner P. (Zootaxa, 2015)
Three new species of the Cape high-mountain stag beetle genus, Colophon Gray (Coleoptera: Lucanidae), from South Africa are described. They are C. deschodti new species, C. switalae new species, and C. struempheri new species. The new taxa fall within a species complex of geographically disjunct entities related to Colophon stokoei Barnard. Furthermore, the mitochondrial COI gene shows a high degree of sequence divergence, with pairwise genetic distances between the species ranging between 7.4–10.7%. The new species are illustrated by photographs. Colophon eastmani nagaii Mizukami is raised to species level on the basis of geographic range and molecular differences between it and the nominate subspecies. This brings the total number of described species in the genus to 21. An updated checklist of the South African species of Colophon is also provided.